A survey of capital budgeting practices used by firms in Barbados. Issue 4 (3rd December 2018) - Alleyne, Philmore; Armstrong, Shantelle; Chandler, Marissa
Abstract : Purpose: This paper aims to examine the capital budgeting practices used by firms in Barbados using contingency theory. Design/methodology/approach: The study involves the use of a self-administered questionnaire sent to the individual responsible for capital budgeting decisions (either the accountant, financial controller or senior manager) in each of the firms selected. In total, 41 completed questionnaires are received; 12 follow-up interviews are conducted with respondents to indicate the reasons for use and non-use of capital budgeting practices. Findings: Capital budgeting practices are not widely used by firms in Barbados. The payback method (PBM) is determined to be the preferred method of choice because of its simplicity, agility and cultural practices. Based on contingency theory, organisations in Barbados believe that the PBM is a better fit for them. Top management drives the capital budgeting process with crude and non-traditional methods for the acceptance of capital projects. While there are no statistically significant differences in the capital budgeting practices used in different sectors, professional accountants are more likely to use net present value and sensitivity analysis than non-professional accountants. Research limitations/implications: The sample is small, and consequently, findings may not be generalisable to the population. Originality/value: This study makes a significant contribution to the body of literature in emerging countries such as Barbados on the usage of capital budgeting practices and factors that may influence their usage. It further contributes to policymakers, practitioners, organisations and stakeholders of organisations.